2019
DOI: 10.1111/myc.12884
|View full text |Cite
|
Sign up to set email alerts
|

Fungal infections of the central nervous system and paranasal sinuses in onco‐haematologic patients. Epidemiological study reporting the diagnostic‐therapeutic approach and outcome in 89 cases

Abstract: Summary Invasive fungal infections (IFI) of the Central Nervous System (IFI‐CNS) and Paranasal Sinuses (IFI‐PS) are rare, life‐threatening infections in haematologic patients, and their management remains a challenge despite the availability of new diagnostic techniques and novel antifungal agents. In addition, analyses of large cohorts of patients focusing on these rare IFI are still lacking. Between January 2010 and December 2016, 89 consecutive cases of Proven (53) or Probable (36) IFI‐CNS (71/89) and IFI‐P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 33 publications
2
61
0
2
Order By: Relevance
“…Fungi have also been associated with other neurological diseases. Recently, an increasing number of opportunistic mycoses of the central nervous system (CNS) has been reported in healthy individuals and, in particular, in patients with sepsis, prolonged ventilation, oncological therapies, organ transplantation, overuse of antibiotics, HIV patients, and others [41,60]. Opportunistic mycoses of CNS are associated with higher morbidity and mortality [61,62] owing to pathogenic fungi such as Cryptococcus neoformans, which are able to cross the otherwise prohibitive blood-brain barrier [41,63].…”
Section: Introductionmentioning
confidence: 99%
“…Fungi have also been associated with other neurological diseases. Recently, an increasing number of opportunistic mycoses of the central nervous system (CNS) has been reported in healthy individuals and, in particular, in patients with sepsis, prolonged ventilation, oncological therapies, organ transplantation, overuse of antibiotics, HIV patients, and others [41,60]. Opportunistic mycoses of CNS are associated with higher morbidity and mortality [61,62] owing to pathogenic fungi such as Cryptococcus neoformans, which are able to cross the otherwise prohibitive blood-brain barrier [41,63].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with aspergillosis within the CNS typically present with focal neurological signs such as pareses or seizures. Overall mortality is still high reaching 69% (with IFD‐attributable mortality 33%) in a recent study from Italy 115 . Comparable studies regarding drug treatment of CNS aspergillosis do not exist, but D‐AmB was found to be not effective 116 .…”
Section: Resultsmentioning
confidence: 99%
“…CNS: CNS infections caused by Candida spp. are extremely rare in adult patients with haematological malignancies 115,170 . Classically, patient groups at risk are (a) very low birth weight infants and (b) patients following neurosurgical interventions 171 .…”
Section: Resultsmentioning
confidence: 99%
“…(67%), następnie przestawiciele Mucorales (28%) oraz Fusarium sp. Połowa przypadków była ograniczona do zatok, a druga połowa miała postać rozsianą [30].…”
Section: Zakażenia Oka Ucha Nosa Gardła I Jamy Ustnej (Eent) W Tyunclassified
“…Wśród czynników etiologicznych dominował Aspergillus sp. (70%), rzadziej stwierdzano rodzaje z rzędu Mucorales (22%), Cryptococcus (4%) i Fusarium (2%) [30]. W 2012 r. wybuchła w USA największa zarejestrowana epidemia zakażeń związanych z zewnątrzoponowymi i dostawowymi iniekcjami octanu metyloprednizolonu (MPA) zanieczyszczonego pleśnią Exserohilum rostratum i kilkoma innymi mikroorganizmami.…”
Section: Zakażenia Ośrodkowego Układu Nerwowego (Cns)unclassified